BMP4 preserves the developmental potential of mESCs through Ube2s- and Chmp4b-mediated chromosomal stability safeguarding. Issue 8 (11th February 2022) - Wang, Mingzhu; Zhao, Kun; Liu, Meng; Wang, Mengting; Qiao, Zhibin; Yi, Shanru; Jiang, Yonghua; Kou, Xiaochen; Zhao, Yanhong; Yin, Jiqing; Li, Tianming; Wang, Hong; et al.
Abstract: Chemically defined medium is widely used for culturing mouse embryonic stem cells (mESCs), in which N2B27 works as a substitution for serum, and GSK3β and MEK inhibitors (2i) help to promote ground-state pluripotency. However, recent studies suggested that MEKi might cause irreversible defects that compromise the developmental potential of mESCs. Here, we demonstrated the deficient bone morphogenetic protein (BMP) signal in the chemically defined condition is one of the main causes for the impaired pluripotency. Mechanistically, activating the BMP signal pathway by BMP4 could safeguard the chromosomal integrity and proliferation capacity of mESCs through regulating downstream targets Ube2s and Chmp4b . More importantly, BMP4 promotes a distinct in vivo developmental potential and a long-term pluripotency preservation. Besides, the pluripotent improvements driven by BMP4 are superior to those by attenuating MEK suppression. Taken together, our study shows appropriate activation of BMP signal is essential for regulating functional pluripotency and reveals that BMP4 should be applied in the serum-free culture system.